Hemorrhagic ascites as a complication of heart failure: A case report and review of the literature. Issue 38 (23rd September 2022) - Abbarh, Shahem; Farwati, Amr; Neffati, Nedia; Habib, Mhd Baraa
Abstract : Introduction: Although ascites is a common complication of congestive heart failure, the association between heart failure and hemorrhagic ascites is quite rare. Patient concerns: A 64-year-old woman with recurrent large bloody ascites secondary to heart failure. Diagnosis: Ascitic fluid assessment revealed red blood cells of 75, 125/mm 3 and white blood cells of 225/mm 3 . The total protein in the ascitic fluid was 28.7 g/L, with a high serum ascites albumin gradient. Peritoneal fluid examinations for bacterial culture, acid-fast bacilli (smear and culture), and malignant cell cytology were negative. Interventions: The patient was managed with therapeutic paracentesis, aggressive diuresis, and optimization of her heart failure medications. Outcomes: The patient's symptoms improved dramatically and was discharged in a stable condition. Conclusion: Congestive heart failure should be considered as a potential cause of hemorrhagic ascites after ruling out other serious causes.